2006
DOI: 10.1017/s0013091504000938
|View full text |Cite
|
Sign up to set email alerts
|

Low-Regularity Solutions for the Ostrovsky Equation

Abstract: The well-posedness of the Ostrovsky equation is considered. Local well-posedness for data iñ H s (R) (s − 1 8 ) and global well-posedness for data inL 2 (R) are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…These lemmas can be also found in [9], however for completeness, we give the proofs of them here. First let us use the following notations…”
Section: Preliminary Estimatesmentioning
confidence: 97%
See 2 more Smart Citations
“…These lemmas can be also found in [9], however for completeness, we give the proofs of them here. First let us use the following notations…”
Section: Preliminary Estimatesmentioning
confidence: 97%
“…In this section, we use the approaches in [9] to obtain the local well-posedness of the problem (1.1)-(1.2). By theL 2 energy equation for the solution, we can obtain the global well-posedness and the existence of the bounded absorbing sets inL 2 .…”
Section: Global Well-posedness Inl 2 and Absorbing Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have investigated the stability of the solitary waves or soliton solutions of (1.2); for instance, see [16][17][18]. Many people have studied the Cauchy problem for (1.2), for instance, see [17,[19][20][21][22][23][24][25][26][27][28][29][30]. The result of [23,25,31] showed that s = - 3 4 is the critical regularity index for (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…It draws much attention of physicists and mathematician. Many people have investigated the Cauchy problem for (1.1), for instance, see [7,[9][10][11][12][13][14][15][16][17][21][22][23][28][29][30]. By using the Fourier restriction norm method introduced in [3,4], Isaza and Mejía [13] proved that (1.1) is locally well-posed in H s (R) with s > − 3 4 in the negative dispersion case and is locally well-posed in H s (R) with s > − 1 2 in the positive dispersion case.…”
Section: Introductionmentioning
confidence: 99%